STATUS AND ANALYSIS OF THE DEVELOPMENT OF WORLD ELECTRONIC TRADE SERVICE - Khamrayeva Sayyora Nasimovna; Olimov Islom Ilkhomovich (Scholar Express Journals, 2021)
The article highlights the role and importance of e-commerce in economic development. The theoretical foundations of the development of electronic trade, its specific features are given. The research paper also highlights the advantages and disadvantages of e-commerce over traditional commerce. The impact of coronavirus Covid-19 on the development of electronic trade was also analyzed based on data from international experts.
Keywords: e-commerce, electronic trade, Chinese experience, pandemic, quarantine, internet, supermarket, hypermarket